Pengembangan Model Pengelolaan Kuliah Bersama Rumpun Mata Kuliah Sama Pada Karakteristik Lembaga Penyelenggara Berbeda - Yerry Soepriyanto; Henry Praherdhiono; Eka Pramono Adi (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2016)
This research was conducted to develop a co-management model between two universities with different characteristics but having the same subject family. The methodology used is a web-based learning design development model. The result of the development is a product in the form of web-based blended learning with an open source platform, standard operating procedures guidelines for server administrators, students during lectures and lecturers as course supervisors.